Pemahaman Pemeriksaan Payudara Sendiri (SADARI) sebagai Upaya Preventif Kanker Payudara pada Remaja Putri - Adriana Sainafat (Yayasan Literasi Sains Indonesia, 2026)
Breast Self-Examination (BSE) is a preventive measure that can be done independently and effectively, especially during adolescence, recommended for women starting at the age of 16-17, to be done independently at home every month. For women who are still menstruating, the examination is done every 7th to 10th day, counted from the first day of menstruation, or monthly on the same date for those who are already menopausal. This study aims to determine the level of knowledge of adolescent girls about BSE as a preventive effort for breast cancer. The type of research used in this study is qualitative research with a descriptive design. The population in this study is all students from grade X to XII at SMA Cor Jesu Larat, with informants consisting of healthcare workers, parents, and 8 adolescent female students. The results of this study also explain how the knowledge and attitudes of adolescent female students, the role of health workers, and the role of parents relate to (SADARI) as a preventive effort for breast cancer. This sufficient knowledge shows that even though most students are already aware of self-breast examination (SADARI), there is still a need to increase education to encourage the practice of regular examinations 4 times a year. It can be concluded that adolescent girls' knowledge about SADARI is considered sufficient. Therefore, it is recommended that schools and health workers provide regular counseling to raise awareness and preventive actions against breast cancer from an early age.